2014
DOI: 10.1371/journal.pone.0082331
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Brain Delivery, and Efficacy in Brain Tumor-Bearing Mice of Glutathione Pegylated Liposomal Doxorubicin (2B3-101)

Abstract: Brain cancer is a devastating disease affecting many people worldwide. Effective treatment with chemotherapeutics is limited due to the presence of the blood-brain barrier (BBB) that tightly regulates the diffusion of endogenous molecules but also xenobiotics. Glutathione pegylated liposomal doxorubicin (2B3-101) is being developed as a new treatment option for patients with brain cancer. It is based on already marketed pegylated liposomal doxorubicin (Doxil®/Caelyx®), with an additional glutathione coating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(138 citation statements)
references
References 46 publications
5
128
1
Order By: Relevance
“…Evidence of increased brain uptake of other drugs using GSH-PEG liposomal preparations has recently been published. The use of the GSH-PEG liposomal system safely increased the brain delivery of doxorubicin in mice, resulting in inhibition of brain tumor growth and improved survival (15). Also, the efficacy of GSH-PEGylated liposomal methylprednisolone was enhanced compared to the use of non-targeted liposomes in a mice EAE model of neuroinflammation (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of increased brain uptake of other drugs using GSH-PEG liposomal preparations has recently been published. The use of the GSH-PEG liposomal system safely increased the brain delivery of doxorubicin in mice, resulting in inhibition of brain tumor growth and improved survival (15). Also, the efficacy of GSH-PEGylated liposomal methylprednisolone was enhanced compared to the use of non-targeted liposomes in a mice EAE model of neuroinflammation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Encapsulation of methylprednisolone in the GSHcoated PEG liposomes improved its therapeutic efficacy in acute experimental autoimmune encephalomyelitis (EAE) in mice compared to that of the drug in non-coated PEG liposomes (14). GSH-PEG liposomes containing doxorubicin also appear to be effective according to preclinical and Phase I clinical cancer trials, and are currently under investigation in a Phase II study (clinicaltrials.gov NCT01386580, NCT01818713) (15,16). Similarly structured PEGylated liposomes have been shown to be a safe, effective drug delivery system in cancer treatment and have been on the market for many years, e.g., containing doxorubicin as the active compound (Doxil®/Caelyx®) (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Additional active targeting using moieties that preferentially bind to receptors on the cerebral endothelial cells or overexpressed on brain tumor cells did indeed improve the therapeutic potential of nanomedicines due to preferential distribution to and within the brain tumor area: in all the studies with intravenously administered actively targeted nanomedicines, the median survival times were longer than their actively untargeted counterparts and noticeably longer than the untreated controls [75,[86][87][88].…”
Section: Systemic Delivery Of Nanomedicinesmentioning
confidence: 97%
“…[50] According to the preclinical studies, 2B3-101 showed a 5-fold enhanced doxorubicin brain delivery versus PLD (Doxil ® ). [99] The company held a phase I/IIa clinical study in patients with solid tumors and brain metastases or recurrent malignant glioma. [100] Nektar develops new drug candidates by utilizing its proprietary 3D 4-armed branched PEGylation and advanced polymer conjugate technologies to modify the chemical structure of various active pharmaceutical ingredients.…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%